DAMPAK RESTRUKTURISASI PINJAMAN UMKM DARI PEMERINTAH DAN DALAM MEMPERCEPAT PEMULIHAN WIRAUSAHA MUDA DI BALI PADA ERA PANDEMI (STUDI KASUS DI LEMBAGA PERKREDITAN DESA (LPD) SIBETAN, KECAMATAN BEBANDEM, KABUPATEN KARANGASEM) - Yusmini, Ni Made; Odik Artawan, I Gede (Unitri Press, 2023)
This research aims to explain the credit restructuring program and the implementation of credit restructuring for MSMEs affected by Covid-19. This research is a qualitative descriptive research, with data sources obtained from observation, interviews, documentation and literature study. The research results show that demand for banking credit during the COVID-19 pandemic at LPD Sibetan has decreased. This study also explains the results of implementing government policies to combat the impact of Covid-19 with the MSME Debtor Restructuring Program at the Sibetan Village Credit Institution (LPD), Uangdem District, Karangasem Regency. Implementation of credit restructuring at LPD Sibetan, Burdendem District, Karangasem Regency, namely: reducing interest rates, extending the term, reducing principal, reducing debt interest, adding capital/credit facilities and converting credit/funding into temporary capital participation. As a result of the implementation of the restructuring plan, the LPD debtor of Sibetan Village issued a restructuring policy or relief given based on data which researchers describe as a 12 month extension which is expected to end in 2026 to 2027 as a countercyclical policy to the impact of the spread of the 2019 corona virus disease.